IMPLEMENTATION OF GREEN BUILDING ASPECTS BASED ON THE GREEN BUILDING COUNCIL INDONESIA: A CASE STUDY IN THE REGIONAL LIBRARY BUILDING OF EAST JAVA PROVINCE - Cindy Alya Cantika; Yudith Vega Paramitadevi (Universitas Pendidikan Indonesia, 2022)
Buildings operational and maintenance can cause an increase in global warming, so it is necessary to apply the concept of green building. Most buildings in Indonesia are old buildings, so the Green Building Council Indonesia issues green building standards for existing buildings. The problems analyzed are the value of implementing green buildings in the Regional Library of East Java Province and recommendations that can be given after the assessment. The study method consisted of field observations, expert interviews, and a questionnaire survey with the Guttman Scale referring to the Greenship Existing Building version 1.0 using 12 of 41 criteria. There are 7 benchmarks for each criterion that have not been met, such as pedestrian facilities, percentage of softscape, provision of non-pet habitat, routine recording on kWh meters, operating and maintenance guides for air conditioning systems and electronic devices, collection and sorting of waste by type, as well as lighting that is less than the standard of SNI 03-6197-2000. The Regional Library of East Java Province received a Greenship Existing Building version 1.0 certification value of 26 points or 53.1% of 49 points. Recommendations are given so that the assessment benchmarks that are still not available can be met.